Геномна мінливість клітинних ліній пшениці, стійких до метаболітів збудника офіобольозу, за дії осмотичного стресу - Зінченко, Марія Олександрівна; Бавол, А. В.; Дубровна, О. В.; Zinchenko, Mariia O.; Bavol, A. V.; Dubrovna, O. V. (Нац. акад. наук України, Ін-т молекул. біол. і генет., Укр. т-во генетиків і селекціонерів ім. М. І. Вавилова, 2013)
Determination of cytogenetic and molecular - genetic polymorphism of resistant/nonresistant to the pathogen metabolites of G. graminis var. tritici cellular lines of bread wheat under osmotic stress and plant–regenerants from them. Methods cytogenetic analysis and IRAP – method. Results. It was found that the effect of mannitol appears with high concentrations and result in increased frequency of aneuploidy and spindle failures. While callus and regenerated plants were cultured in vitro, in the spectra of the DNA amplification products noted the appearance of amplicon approximately 638 bp. length, which is absent in original form. Conclusions. We found that, depending on the scheme used cell selection (direct or step) can identify the different changes in the genome.
Variability of genome of wheat cellular lines resistant to metabolites of ophiobolus root rot under osmotic stress, and plant - regenerants from them
Keywords: мінливість; гіперосмолярність; cellular lines; IRAP – method; Triticum aestivum L.; cytogenetic effect